2018
DOI: 10.3892/ijo.2018.4365
|View full text |Cite
|
Sign up to set email alerts
|

Survivin knockdown induces senescence in TTF‑1-expressing, KRAS-mutant lung adenocarcinomas

Abstract: Survivin plays a key role in regulating the cell cycle and apoptosis, and is highly expressed in the majority of malignant tumors. However, little is known about the roles of survivin in KRAS-mutant lung adenocarcinomas. In the present study, we examined 28 KRAS-mutant lung adenocarcinoma tissues and two KRAS-mutant lung adenocarcinoma cell lines, H358 and H441, in order to elucidate the potential of survivin as a therapeutic target. We found that 19 (68%) of the 28 KRAS-mutant lung adenocarcinomas were differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…Shanzhi et al found that the levels of TTF‐1 expression may guide clinical therapy for LUAD with EGFR mutations . Moreover, in a previous study, lung adenocarcinoma with KRAS mutation has been found to depend on TTF‐1 expression for growth and to possibly be regulated by survivin protein . More studies are needed to elucidate the role of TTF‐1 in the process of PMA.…”
Section: Discussionmentioning
confidence: 97%
“…Shanzhi et al found that the levels of TTF‐1 expression may guide clinical therapy for LUAD with EGFR mutations . Moreover, in a previous study, lung adenocarcinoma with KRAS mutation has been found to depend on TTF‐1 expression for growth and to possibly be regulated by survivin protein . More studies are needed to elucidate the role of TTF‐1 in the process of PMA.…”
Section: Discussionmentioning
confidence: 97%
“…The 3D cell culture aims at recapitulating in vivo tissue architectures to provide physiologically relevant models to study normal development and disease [ 74 , 75 ]. Alt-hough the 3D culture model cannot fully recapitulate all aspects of the in vivo environment, it offers more benefits than a 2D culture.…”
Section: Discussionmentioning
confidence: 99%
“…Survivin, an antiapoptotic protein, is overexpressed in several types of cancer, and knockdown of Survivin induces cell apoptosis by increasing Bad and Bax expression and inducing G2/M arrest (6). Additionally, in an in vivo xenograft model of KRAS-mutant lung adenocarcinoma, Survivin knockdown and trametinib treatment induced cell death (7). Moreover, in hepatocellular carcinoma cells, treatment with ATB-263, a novel Bcl-2 inhibitor, and silencing of Survivin induced cell apoptosis; these results implied that Survivin knockdown is an important method to overcome the hurdle of drug resistance in cancer therapy (8), and the development of a method for silencing Survivin is urgently needed.…”
Section: Introductionmentioning
confidence: 99%